Polydom Is an Extracellular Matrix Protein Involved in Lymphatic Vessel Remodeling. Issue 8 (14th April 2017) - Morooka, Nanami; Futaki, Sugiko; Sato-Nishiuchi, Ryoko; Nishino, Masafumi; Totani, Yuta; Shimono, Chisei; Nakano, Itsuko; Nakajima, Hiroyuki; Mochizuki, Naoki; Sekiguchi, Kiyotoshi
Abstract : Rationale: : Lymphatic vasculature constitutes a second vascular system essential for immune surveillance and tissue fluid homeostasis. Maturation of the hierarchical vascular structure, with a highly branched network of capillaries and ducts, is crucial for its function. Environmental cues mediate the remodeling process, but the mechanism that underlies this process is largely unknown. Objective: : Polydom (also called Svep1) is an extracellular matrix protein identified as a high-affinity ligand for integrin α9β1. However, its physiological function is unclear. Here, we investigated the role of Polydom in lymphatic development. Methods and Results: : We generated Polydom-deficient mice. Polydom −/− mice showed severe edema and died immediately after birth because of respiratory failure. We found that although a primitive lymphatic plexus was formed, it failed to undergo remodeling in Polydom −/− embryos, including sprouting of new capillaries and formation of collecting lymphatic vessels. Impaired lymphatic development was also observed after knockdown/knockout of polydom in zebrafish. Polydom was deposited around lymphatic vessels, but secreted from surrounding mesenchymal cells. Expression of Foxc2 (forkhead box protein c2), a transcription factor involved in lymphatic remodeling, was decreased in Polydom −/− mice. Polydom bound to the lymphangiogenic factor Ang-2 (angiopoietin-2), which was found to upregulate Foxc2 expression in cultured lymphatic endothelial cells. Expressions of Tie1/Tie2 receptors for angiopoietins were also decreased in Polydom −/− mice. Conclusions: : Polydom affects remodeling of lymphatic vessels in both mouse and zebrafish. Polydom deposited around lymphatic vessels seems to ensure Foxc2 upregulation in lymphatic endothelial cells, possibly via the Ang-2 and Tie1/Tie2 receptor system. Abstract : Supplemental Digital Content is available in the text.